KELAYAKAN BOOKLET BERBASIS PROBLEM SOLVING PADA MATERI REAKSI REDUKSI DAN OKSIDASI - Renaningtyas, Agneviana Pratikta Ditya; Enawaty, Eny; Erlina, Erlina; Masriani, Masriani; Rasmawan, Rahmat (EduChem, 2024)
The purpose of this study was to determine the level of feasibility of the developed booklet based on expert judgment. This research and development (RD) method adopts the ADDIE development model. Validation forms were used as data collection tools. The criteria in the questionnaire were assessed using the Likert scale, which was designed to measure the effectiveness of the product to be developed. The results of the expert evaluation (expert judgment) show that the interpretation is very accurate, with 95.6% feasibility in content, 91.7% in graphics, and 100% in language. It can be concluded that the problem solving handbook on reduction and oxidation reaction materials is suitable for students of SMA Negeri 5 Pontianak.